Expediente e apresentação da edição - v. 16, n. 3 - Dias, Chiara Maria Seidel Luciano; Petry, Polyanna Possani da Costa; Troian, Thiélide Verônica da Silva Pavanelli; Siebiger, Ralf Hermes (Eventos Pedagógicos, 2026)
Expediente e apresentação da edição - v. 16, n. 3, nov./dez. 2025.